2013
DOI: 10.1186/cc13103
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation for acute hypoxemic respiratory failure: intubation rate and risk factors

Abstract: IntroductionWe assessed rates and predictive factors of non-invasive ventilation (NIV) failure in patients admitted to the intensive care unit (ICU) for non-hypercapnic acute hypoxemic respiratory failure (AHRF).MethodsThis is an observational cohort study using data prospectively collected over a three-year period in a medical ICU of a university hospital.ResultsAmong 113 patients receiving NIV for AHRF, 82 had acute respiratory distress syndrome (ARDS) and 31 had non-ARDS. Intubation rates significantly diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
156
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(174 citation statements)
references
References 27 publications
11
156
2
5
Order By: Relevance
“…Similar to previous reports [19,20], ARDS or cancer patients were associated with more frequent NIV failure, while heart failure was associated with less frequent treatment failure and pneumonia with an intermediate failure rate.…”
supporting
confidence: 89%
“…Similar to previous reports [19,20], ARDS or cancer patients were associated with more frequent NIV failure, while heart failure was associated with less frequent treatment failure and pneumonia with an intermediate failure rate.…”
supporting
confidence: 89%
“…Similarly poor outcomes have been observed in cohort studies of ARDS patients treated with NIV (40,41), who represented a majority (almost 70%) of patients with hypoxemic ARF (26,39). Another limitation for NIV in hypoxemic ARF is the high mortality rate (50%) in case of NIV failure (1,39). In the recent large-scale international LUNG SAFE study, severe hypoxemic patients who failed NIV had a higher mortality rate (approximately 43%) than invasively ventilated patients (42).…”
Section: Hypoxemic Arfmentioning
confidence: 81%
“…More recently, cohort studies including patients treated with NIV for hypoxemic ARF reported a high intubation rate, potentially exceeding 50% (39). Similarly poor outcomes have been observed in cohort studies of ARDS patients treated with NIV (40,41), who represented a majority (almost 70%) of patients with hypoxemic ARF (26,39). Another limitation for NIV in hypoxemic ARF is the high mortality rate (50%) in case of NIV failure (1,39).…”
Section: Hypoxemic Arfmentioning
confidence: 99%
See 2 more Smart Citations